The use of Yo-Yo intermittent recovery test level 1 for the estimation of maximal oxygen uptake in youth elite soccer players - Michailidis, Yiannis; Chavlis, Stelios; Mitrotasios, Michalis; Ispirlidis, Ioannis; Vardakis, Lazaros; Margonis, Konstantinos; Mikikis, Dimitrios; Mandroukas, Athanasios; Mavrommatis, George; Metaxas, Thomas (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Researchers have proposed some equations for the estimation of VO2max in adults with the use of the total distance or the maximum velocity of the Yo-Yo test. However, the use of these equations for estimating the VO2max in children may include mistakes. Their physiological adaptations to incremental exercise are different than in adults. Aim of Study. The purpose of this study was to investigate the relationship between a) the predicted VO2max (by a published equation) with the VO2max measured in the laboratory and b) the velocity at the last stage of Yo-Yo IR1 (YYIR1) with the vVO2max measured in the laboratory in elite youth soccer players (U17). Material and Methods. Twenty-seven soccer players completed a laboratory treadmill test (LTT) and the YYIR1 which were conducted in random order. Their VO2max was measured during LTT and had been predicted by the results of the YYIR1 test from a published equation. Results. The values of VO2max in LTT and YYIR1 were different (t = –7.652, p < 0.001) (58.9 ± ± 5.3 and 50.8 ± 2.7 ml/kg/min, respectively). There were no differences between the measured values of vVO2max in LTT and YYIR1 (t = 1.652, p = 0.11). Also, no differences were observed in HRmax values in the two tests (t = –0.185, p = 0.854). The equation derived from the results of the present study did not have prediction power (r = 0.11, r2 = 0.012). Conclusions. The VO2max which was predicted by the published equation from the performance of YYIR1 was different from VO2max was measured in the laboratory in elite youth male soccer players (U17). However, YYIR1 could be used for measuring HRmax and VO2max velocity
Keywords: aerobic capacity, football, prediction, maximal oxygen consumption; football; prediction; maximal oxygen consumption